PEMIMPIN DAN KEPEMIMPINAN DALAM AL-QUR’AN - Surahman Amin; Ferry Muhammadsyah Siregar (Sekolah Tinggi Agama Islam (STAI) Sadra, 2015)
This paper discusses about leader and leadership in the Quran. It also focuses on the study of leadership, its ethical and practical aspects. It aims at exploring the meaning of leader and leadership in the Quran. In addition, the Quranic verses and its words are collected and analyzed. This paper uses the theory of tafsir, especially tafsir maudhui and the heuristic method for collecting the data. It is found that the Quranic verses are divided into Madaniyah and Makkiyah. It uses the term “khalīfah” (caliphate), “imāmah” (imamate), and “ulu al-amr” and its derivatives.